PENERAPAN MODEL PEMBELAJARAN AKTIF TIPE KELOMPOK BELAJAR PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VIII SMPN 2 IV JURAI KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2012/2013 - Maizelianto, Epin; K, Delsi; Fitri, Dewi Yuliana (STKIP PGRI Sumbar, 2013)
In this research , as background of the study is low achievement of student in SMPN 2 IV Jurai. The purpose of study is to determine: whether are the result of using active instructional model as type learning group is better then using the conventional learning. The kind of study is experimental research. Population of the study was VIII grade of SMPN 2 IV Jurai especially academic years 2012/2013. The researcher chosen the sample by using random sampling technique, the samples were VIII.1 and VIII.2. the instrument that had been used for collecting data is by giving achievement test. The test is essay form that has reliability about = 0,89. In addition, analyzing data that had been done by using t test. Based on the hypothesis testing is gotten P-value = 0,008 < . In this case, the hypothesis can be received. It can be concluded that using the type of group learning model is better than using conventional learning in teaching process.